Enhanced random lasing from a colloidal CdSe quantum dot-Rh6G system. (9th January 2015) - Augustine, Anju K; Radhakrishnan, P; Nampoori, V P N; Kailasnath, M
Abstract: In this letter, we report random laser action in a system where optical amplification is provided by colloidal CdSe quantum dots (CQDs) triggered by the emission from Rhodamine 6G. The laser emission from CdSe QDs is optically excited by Rh-6G which in turn is photo-pumped by a frequency-doubled Q-switched Nd : YAG laser system at an excitation wavelength of 532 nm. At intensities greater than the threshold value, laser emission is characterized by narrowing peaks.